(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status of myopia and associated factors among 300 children aged 3-18 years presenting to Hanoi Eye Hospital in 2025. Subjects and methods: A cross-sectional descriptive study was conducted on 300 children. Study variables included demographic and clinical characteristics, vision-related lifestyle habits, eye care practices, and the impact of myopia on daily activities. Results: Most children experienced mild impact on daily activities (67%), while 10% were severely affected. Spectacles were the main treatment modality (79.67%); however, 12.67% of children had not received any treatment. The most common duration of electronic device use was 2-4 hours per day (33%), and 39% used devices for more than 4 hours daily. Only 31.66% spent more than 1 hour per day on outdoor activities. Near reading at a close distance was common (81.67%), and 19.33% did not undergo regular eye examinations. Conclusions: Myopia remains prevalent among children and is associated with visual behaviors. These findings highlight the importance of early detection, regular monitoring, and comprehensive interventions to limit progression and prevent complications.